1996
DOI: 10.1210/endo.137.2.8593803
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in cellular expression and functions of melanin-concentrating hormone and atrial natriuretic factor in the rat digestive tract.

Abstract: Melanin-concentrating hormone (MCH) is a cyclic peptide isolated first from salmon brain, then from rat and human hypothalamus. We have recently found expression of MCH messenger RNA and encoded peptides, e.g. MCH and neuropeptide-glutamic acid-isoleucine, within the rat gastrointestinal (GI) tract, but their cellular origin was unclear. Furthermore, similarities in the localization of rat atrial natriuretic factor (ANF) and rat MCH immunoreactivities within intestine suggested functional convergence. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…In the gut, likely sources of MCH are the enteric nervous system, enterochromaffin cells, and resident or infiltrating immune cells, based on evidence described here (Fig. 4) and in previous reports (10,(12)(13)(14)42).…”
Section: Discussionsupporting
confidence: 64%
“…In the gut, likely sources of MCH are the enteric nervous system, enterochromaffin cells, and resident or infiltrating immune cells, based on evidence described here (Fig. 4) and in previous reports (10,(12)(13)(14)42).…”
Section: Discussionsupporting
confidence: 64%
“…Other physiological roles of MCH include regulation of the hypothalamopituitary adrenal gland axis (11), modulation of water and electrolyte fluxes in the gut (12), stimulation of oxytocin secretion from isolated rat neurohypophysis (13), regulation of sensory processing (14), and modulation of monoaminergic activity in the medial preoptic area (15). In addition, several lines of evidence also suggest a role for MCH in modification of memory retention (16), modulation of other hormones regulating food intake (17) and sexual behavior (18) and involvement in seizure (19).…”
Section: Melanin-concentrating Hormone (Mch)mentioning
confidence: 99%
“…Our own group has demonstrated MCH and MCHR1 immunoreactivity in the rat myenteric and submucosal plexus (24), whereas others have shown that vagal afferent neurons in both human and rat express MCH and its G protein-coupled seven-transmembrane receptor (MCHR1) (6). Moreover, when tested in an in situ ligated loop experiment, MCH stimulated Na ϩ and K ϩ fluxes in proximal colon; water, as well as Na ϩ and K ϩ fluxes in duodenum; and bicarbonate absorption in the jejunum (20).…”
mentioning
confidence: 99%